1983
DOI: 10.1128/mcb.3.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Construction and use of a dominant, selectable marker: a Harvey sarcoma virus-dihydrofolate reductase chimera.

Abstract: The transcriptional promoter of the Harvey sarcoma virus long terminal repeat has been used to construct a biologically active dihydrofolate reductase chimera. The construction placed the long terminal repeat at the 5' end of a dihydrofolate reductase cDNA. This chimera mediated methotrexate resistance when introduced into wild-type NIH3T3 mouse cells by transfection. The chimeric sequences were expressed in the form of polyadenylated RNA and dihydrofolate reductase protein and were amplified when the methotre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Plasmid pMUD1 was constructed by inserting the gene encoding the murine DHFR, amplified by PCR from plasmid pLTRdhfr26 (Murray et al, 1983), into plasmid pJMB100A. The PCR primers introduced a unique NcoI site at the 5′ end of the gene and a unique XbaI site at the 3′ end of the gene.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pMUD1 was constructed by inserting the gene encoding the murine DHFR, amplified by PCR from plasmid pLTRdhfr26 (Murray et al, 1983), into plasmid pJMB100A. The PCR primers introduced a unique NcoI site at the 5′ end of the gene and a unique XbaI site at the 3′ end of the gene.…”
Section: Methodsmentioning
confidence: 99%
“…D-dot hybridization analysis (Fig. SB) indicated that there were an average of 20 and 1,150 copies of pdhOD1 per cell in the initial and final DFMO-resistant populations, respectively. Southern blot analysis (Fig.…”
Section: Expression Of Heterologousmentioning
confidence: 99%
“…Amplification vectors based on dihydrofolate reductase (dhfr) can be used to obtain high levels of expression of a variety of heterologous genes, since genes linked to it can be coamplified and thus overexpressed (14,15,18,34). However, amplification of dhfr-based vectors is generally limited to DHFR-deficient Chinese hamster ovary (CHO) cells, and dominant vectors based on dhfr have reduced ability to amplify (20,27). An amplifiable vector based on adenosine deaminase (ADA) (13) is more easily used in wild-type cells.…”
mentioning
confidence: 99%
“…Amplification ofthis MTX-resistantDHFR is limited due to the higher concentrations of MTX required as a result of the increased Ki of the mutant DHFR. An alternative approach has been the use of a very efficient DHFR expression vector (17). In this case it has been difficult to obtain the optimal MTX concentration necessary for the selection ofthe foreign DHFR gene.…”
mentioning
confidence: 99%